Some Welfare Economics of Working Time - Felix FitzRoy; Jim Jin (Institute of Labor Economics (IZA), 2021)
Few skilled workers in the UK have flexible working time – GPs are the exception – most can only choose between unemployment, or full-time work, which has changed little in recent years, while part time work is mainly unskilled. This market rigidity imposes major welfare losses, in contrast to flexibility of worktime for all in the Netherlands, which has the best work-life balance. Stagnating real wages and rising employer market power and inequality follow declining unionisation, but a standard four-day week, tax reform, basic income, and flexibility rights for all could reverse these trends and provide major welfare gains.
Keywords: D63; J22; H23; 330; working hours; relative income; labour share; basic income